Biological Activity and Characterization of Volatile Compounds of Teucrium orientale Var. glabrescens by SPME and GC‐FID/MS. Issue 1 (13th June 2016) - Yildirmiş, Sermet; Aliyazicioglu, Rezzan; Emre Eyupoglu, Ozan; Ozgen, Ufuk; Alpay Karaoglu, Sengul
Abstract: This study describes the constituents of phenolic acids, volatile components, antioxidant and antimicrobial activities of Teucrium orientale var. glabrescens . Antioxidant activity of methanolic and aquous extracts were examined by three different methods, namely ferric reducing antioxidant power, cupric reducing antioxidant capacity and 2, 2‐diphenylpicrylhydrazyl radical scavenging activity. The phenolic constituents were also determined by reverse phase‐high performance liquid chromatography. Solid phase microextraction of Teucrium orientale var. glabrescens was analyzed by Gas Chromatography‐Flame Ionization Dedector/Mass Spectromerty, Solid‐Phase Microextraction (GC‐FID/MS, SPME). The antimicrobial activity was studied by agar diffusion method. Extracts showed strong antioxidant and antimicrobial activity and contained large amounts of antioxidant compounds. Rosmarinic acid, p‐ coumaric acid and p‐ hydroxybenzoic acid were detected in methanolic extract of plant. Aquous extract was especially effective against Mycobacterium smegmatis . The main chemical classes identified consisted of aldehydes (32.5%), hydrocarbons (29.8%) and monoterpene hydrocarbons (29.8%). Common volatile components of plant detected included nonanal, thuja‐2, 4 (10)‐diene and tetracosane. Practical Applications: Medicinal plants are natural resources used in the treatment of various ailments. Teucrium species have been widely used in folk medicine as a remedy for gastritis, parasitic worms, colds, digestive ulcers, etc. Teucrium species are the subject of growing interest because of their biological properties. Although studies on screening the antimicrobial, and antioxidant activity of the Teucrium species have been done densely, studies on phenolic compounds of Teucrium orientale var. glabrescens are very limited. Teucrium orientale var. glabrescens extracts studied proved to be a good source of antioxidants, antimicrobial agents and volatile components that might serve to protect health and fight against several diseases.